Small and Medium Scale Enterprises’ Activities and Eonomic Developmemnt in Obio-Akpor Local Government Area, Rivers State, Nigeria - Chidume, Ukamaka P.; Nenbee, Simeon G. (Mediterranean Journal of Social Sciences, 2022)
This paper assesses the impact of Small and Medium Scale Enterprises (SMEs) activities on economic development in Obio-Akpor Local Government Area of Rivers State, Nigeria. To achieve this theme, an instrument Called Small and Medium Scale Enterprises Survey Questionnaire (SMEQ) was developed which focused more on employment generation and poverty reduction. The population of the study was chosen based on the two thousand six hundred and thirty-four (2634) registered SMEs with the Rivers State Ministry of Commerce and Industry in 2019. Based on simple random sampling technique, a total of three hundred and thirty-eight (338) respondents were sampled. Relying on descriptive statistics and logistic regression estimation techniques, the data were analyzed. Analyses of the respondents’ opinion suggest that the major businesses engaged in the study area were restaurant, tailoring and beauty/hair dressing. Again, majority of the respondents were of the opinion that SMEs operators do not have increased access to basic social-economic amenities. The output of the logistic regression result has it that an increase in firm size can improve the chances of SMEs fostering economic development in Obio-Akpor while increase in the salary of employees could also enhance the chances of SMEs to redress the rising poverty level too. The paper thus recommends that employment tax incentives should be granted to proprietors of SMEs and taming of the rising insecurity cases across the country. Received: 11 September 2021 / Accepted: 25 November 2021 / Published: 5 January 2022